PEMBELAJARAN BERBASIS MULTIKULTURAL DALAM KEBERAGAMAN SISWA SEKOLAH DASAR - Sirait, Eunike; Zakiah, Linda; Syahda Agtyasha, Gardina; Suhailah Fadjrin, Raihan; Jaya, Indra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article is the result of a literature study that aims to examine multicultural-based learning in the diversity of elementary school students. This research is motivated by the diversity of students in elementary schools so that the role of education is very important by implementing multicultural-based learning. The method used in this research is descriptive qualitative research in the form of a literature review of ten articles obtained from a number of databases. The results of the literature study show that elementary schools have students with diverse conditions, the cultivation of multicultural values is very important to minimize the negative impact of individual differences. Based on these conditions, multicultural-based learning has an important role to be taught to both normal and special needs students. The application of multicultural-based learning can foster awareness of the diversity that exists in students. Multicultural-based learning is expected to be supported by all elements of the elementary school community. The implementation of multicultural-based learning is expected to be implemented well by all parties such as teachers and other educational actors.